ANALISIS X-RAY DIFFRACTION (XRD) TERHADAP VARIASI CAMPURAN ABU VULKANIK DAN SEMEN SEBAGAI BAHAN PEMBENTUK BETON - Hafiza, Jana; Habirun, Asiya Nurhasanah; Zulhedi, Zulhedi; Kurniawan, Deddy (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Volcanic ash contains mineral chemical elements such as Aluminum (Al), Silica (Si), Iron (Fe), Calcium (Ca), and Magnesium (Mg) which have bonding force when mixed with cement. This research aims to look at the presentation of the use of volcanic ash as a concrete construction material. The volcanic ash used was obtained from the eruption of Mount Marapi, West Sumatra, which was then mixed with Portland cement with a composition of mixing volcanic ash and cement 10% + 90%, 20% + 80%, and 30% + 70%, those characteristics were then seen based on spectrometric analysis. X-ray Diffraction (XRD). Based on the XRD test results, it can be seen that the volcanic ash from Mount Marapi, West Sumatra, has a composition of silica (SiO2) and alumina (Al2O3) which is proven to have pozzolanic properties. From the three mixtures, it can be seen that the highest XRD’s peak is quartz because of the high content of silica and oxide. These three mixing variables have been proven to be used as the basis for mixing for concrete formation. Keywords: Volcanic Ash, Mixing, Cement, XRD